Annual ring width in the Mediterranean-alpine shrub species Cytisus galianoi - dataset from long-term alpine ecosystem research in the Sierra Nevada, Spain (LTAER-ES) - Albrecht, Eike Corina; Dobbert, Svenja; Pape, Roland; Wundram, Dirk; Löffler, Jörg (ERDKUNDE, 2023)
This is a datapaper including microscopically measured data of annual ring widths from the Mediterranean-alpine shrub species Cytisus galianoi (Sierra Nevada, Spain). The dataset will be updated with future measurements.